1983_11 The Daily Collegian November 1983 - Associated Students of Fresno State::::::::: (Associated Students of Fresno State, Fresno, Calif.)
Daily (except weedends) during the school year. Microfilm. Palo Alto, Calif.: BMI Library Microfilms, 1986- microfilm reels; 35 mm. Vol.1, no.1 (Feb 8, 1922)-